Formula Jamu Antihipertensi and captopril are equally effective in patients with hypertension - Hussaana, Atina; Sarosa, Hadi; Indrayani, Ulfah Dian; Chodidjah, Chodidjah; Widiyanto, Bagas; Pertiwi, Danis (Universa Medicina, 2016)
BACKGROUNDHypertension is the main cause of morbidity and mortality associated with cardiovascular diseases. Many herbs/spices appear to have significant effects in favorably modulating high blood pressure. A jamu formulation containing 6 plant extracts, Formula Jamu Antihipertensi (FJA), has been described previously. This research study aimed to evaluate the effect of FJA as antihypertensive agent in mild to moderate hypertensive patients. METHODSThis double-blind experimental study was conducted in 40 hypertensive patients, who were randomized into two groups. The first group was treated with oral administration of 2 g FJA and the second group 25 mg captopril daily for 4 weeks. Systolic and diastolic blood pressure as well as liver and kidney function were followed up every week. Independent- t test and two-way ANOVA were used to analyze the data with a level of significance of 0.05.RESULTSThe results showed that after the treatment, FJA and captopril were capable of significantly decreasing systolic and diastolic blood pressure (p <0.05). The decrease in systolic blood pressure between the two groups was identical (p>0.05), while the decrease in diastolic blood pressure was greater in the FJA group than in the captopril group (p <0.05). CONCLUSIONFrom this study it may be concluded that administration of FJA for 4 weeks is equally effective as captopril in reducing systolic and diastolic blood pressure in patients with mild and moderate hypertension. Thus, natural plants and herbs can be our source of drugs, with fewer side effects and better bioavailability for treatment of hypertension in the future.